Secondary minerals of Fe, Pb, Cu in sulfide-containing tailings: sequence of formation, electrochemical reactions and physicochemical model (Talmovskie Sands, Salaire, Russia) - Shavekina Alfiia; Bortnikova Svetlana; Gaskova Olga; Volynkin Sergey; Kalinin Yuri (Russian Journal of Earth Sciences)
The paper presents the results of studies of the composition of secondary Fe, Pb, Cu minerals, formed in contrasting physico-chemical conditions of the stockpiled tailings from the enrichment of Salair barite-polymetallic ores (West Siberia, Russia). The complex mineral composition of ores containing pyrite, chalcopyrite, sphalerite, galena, fahlore, and long-term chemical weathering contributed to the formation of monomineral and zonal secondary rims and fillings of the intergranular space, which were identified using modern research methods. Plumbojarosite, anglesite, cerussite, and iron hydroxides are predominant among them; pyromorphite, hinsdalite, and covellite are less abundant. Thermodynamic modeling was used to solve the inverse problem of restoring the composition of solutions that led to a sequence change in associations of secondary minerals. The observed processes are determined not only by chemical interaction, but also by electrochemical reactions in the systems under consideration, where various mineral components act as galvanic couples. These two processes, combined with the physicochemical parameters of the environment (pH, Eh, ionic composition of solutions), lead to stepwise or incomplete oxidation of the original minerals, followed by selective deposition of the secondary compounds.